Golddiggers, farmers, and traders in the "Chinese districts" of West Kalimantan, Indonesia - Somers Heidhues, Mary F. (Studies on Southeast Asia ;, 2003)
This study examines the changing role of the Chinese community of West Kalimantan, particularly its economic and social relationships. Heidhues explores the history of the community from the early nineteenth century establishment of the kongsis to the "Dayak Raids," which uprooted the rural Chinese population in the 1960s.